(untitled) (Journal of Philosophy, Culture and Political Science, 2024)
The article examines conceptual and methodological issues related to various foundations of national identity. In Kazakhstan, there is a “dialogue” between ethnic and civil identities. Some experts on national identity emphasize the ethnic component, while others include the phenomenon of citizenship. These discussions reflect the experience of national politics, the Soviet paradigm of the national question and the long pause in the official interpretation of this concept. The purpose of this article is to determine the characteristics of the concepts of national identity and identify the factors that shape them. A review of the concepts will allow us to imagine the dynamics and prospects of state building, where there is a creative reworking of narratives, political rhetoric and conditions. Approaches to conceptualizing national identity are based on several factors, starting with the weakening of state mechanisms and the strengthening of the role of language and culture. The study is based on theoretical approaches developed by national and foreign researchers. Official historiography, state symbols, religion, modern culture, media and architecture together constitute an ethno-national trend of state building, within which the role of the Kazakh language and bilingualism is becoming increasingly prominent. The theoretical and practical significance of the article lies in deepening the understanding of the theoretical foundations of national identity, thereby enriching our understanding of the main components of the phenomenon being studied. Examination of various concepts reveals a multifaceted and evolving relationship between factors that contribute to the legitimation of national identity. The article is intended for academic, civic and political audiences and addresses a range of topics related to the dialogic process of nation-building. The article uses secondary research data from both domestic and foreign researchers. This article was prepared within the framework of the IRN AP19680642 research project "Globalization and glocalization in the transformation of the identity of Kazakhstani youth" under the grant financing program of the Ministry of Science and Higher Education of the Republic of Kazakhstan. Key words: national identity, ethnic and civil identity, religious and linguistic identity, nation- building, globalization